Quality Evaluation of Orange Peel (Flavedo) incorporated Ice Cream - K. V. Ananthakumar; B. Dhanalakshmi; T. R. Pugazhenthi (Indian Journal of Veterinary and Animal Sciences Research, 2025)
By-products of fruits possess antioxidant polyphenols, anti-mutagenic, cardio preventive and antiviral activities. The consumers are aware of the health benefits of nutraceutical foods and the demand for such foods is increasing in recent years. Orange peels are rich in flavanones, powerful antioxidants that help to reduce oxidative damage and fight free radicals. Hence, an attempt was made to develop a value added ice cream with orange peel. Orange peel powder was incorporated in ice cream at varying levels viz. 1.5, 2.5, 3.5 and 5 per cent. Based on texture, sensory attributes and physio-chemical properties, sensory evaluation of the product revealed that incorporation of orange peel powder at 2.5% level found to be acceptable.